Criatividade na perspectiva distribuída de Vlad Glăveanu - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This work aims to analyse the distributed perspective of creativity through the work 'Distributed Creativity: Thinking Outside the Box of the Creative Individual' by Vlad Glăveanu (2014), based on the Discursive Textual Analysis of Moraes and Galiazzi (2020). Glăveanu's distributed perspective of creativity assumes that human cognition is not confined to brain processes, but extends and distributes to sociocultural systems of norms, beliefs, and practices where concrete human actions in the world are mediated by artifacts and combined with symbolic actions. It is on this complex "stage" that co-creations are situated, not confined to people or artifacts, and not static in the here-and-now, but distributed in the network of interactions between people, artifacts, and processes that temporally connect them and act in their transformations. The analysis process resulted in two final categories: Expansion of the concept of creativity; and Creativity and Distributed Cognition. The produced metatext focuses on the discussion of the expansion of the concept of creativity through the social, material, and temporal distribution of creativity, as well as on the relationship between the conception of distributed cognition and the expansion of the concept of creativity. Furthermore, the work discusses implications for science education from the distributed perspective of creativity.
Keywords: Criatividade distribuída; Análise Textual Discursiva; Ensino de Ciências; Distributed creativity; Discursive Textual Analysis; Science Teaching; CNPQ::CIENCIAS EXATAS E DA TERRA